Physical Activities of Working Communities During the COVID-19 Pandemic With Hypertension Incidence in Indralaya District (Jurnal Ilmu Kesehatan Masyarakat, 2023)
According to WHO, one in three people in the world suffers from hypertension. Riskesdas results showed that the prevalence of hypertension in Indonesia has increased to 34.1% in 2018. In Ogan Ilir Regency, there had been an increase in cases of hypertension during the Covid-19 pandemic. One important factor was physical activity. The purpose of this study aimed to determine the relationship between physical activity and the incidence of hypertension in workers. The design of this research was a quantitative study with a cross-sectional study design. The population was all workers aged over 25 years in Ogan Ilir district. The sample in this study were workers aged 25 years and lived in Indralaya, namely 100 respondents. The sampling technique was purposive sampling. Data analysis used the chi square test and multiple logistic regression risk factor models. The results of the bivariate analysis showed a relationship between physical activity variables, age, consumption of salty foods, consumption of fatty foods, central obesity, sleep quality, and stress variable with hypertension (p-value <0.05). The results of the multivariate analysis showed a significant relationship between physical activity and hypertension after controlling for the consumption of fatty foods, central obesity and sleep quality (PR 2 4.29; 95% CI: 4.68 – 125.98). Lack of physical activity was a risk factor for hypertension in workers. It was important to prevent hypertension by getting used to moderate-intensity physical activity for at least 30 minutes a day such as cleaning the house, walking, and exercising.